Componentes que afetam a repetição de prenhez de Charolês e Nelore no Sul do Brasil - Joner, Guilherme (2017)
The reproductive efficiency of the herd is highlighted by the productive increase in the production of beef cattle, being responsible for the number of animals that will be available for commercialization and / or termination. There is thus an increase in the selection pressure of the stockholding matrices and the ownership rate of enjoyment. The main obstacle to reproductive efficiency consists in obtaining the calving repetition of matrices, mainly primiparous, because they present variations of body weight and body condition score during their reproductive life. The objective of this study w as to evaluate the live weight and body condition score, measured in different stages of growth, on the rearing of cows with different genetic and contemporary groups. Nellore and Charolais crossbred females born between 2004 and 2010 were evaluated. Heife rs enter the reproductive process with an average age of 26 months, all of them from the same herd and receiving the same management from birth. The food management consisted of forage base of the native field, being only used fodder cultivated in the firs t summer and winter. The female mating season consisted of 90 days, the first 45 days for artificial insemination and the other 45 days for the natural mating with bulls. For the accomplishment of this study were used of the database to the measurements of the female in different moments, in the pre and post calving. The data / groups were submitted to analysis of variance and F test, by PROC GLM and means, compared by Student's t test, α = 0.05 probability. The body weight of the heifer at 24 months showed a negative correlation with the first calving season ( 0.30; P=0.0038). First calf cow who repeated their calves had a greater live weight at weaning (361 kg vs. 333 kg; P=0.0262) than those who did not repeat calves, although there was similar live weight at calving (344 kg vs. 332 kg, P=0.11512). The Nellore genetic predominance when they calved with similar body condition score (2.40 pt e 2.49 pt; P>0,05) and showed negative gains at calving weaning period ( 3.0 kg and 2.1 kg) showed different behaviors, where they did not repeat calves, when they calved (358 kg vs. 399 kg; P<0,05) and weaned (355 kg vs. 397 kg; P<0,05) with smaller body weight. First calf cows that calving with the same body condition score are dependent on positive live weight gain by the end of the next mating season, especially during the calving weaning period. Cows that have the early calving within the calving season are more likely to repeat calves, and multip arous cows have an advantage over first calf cows because they have the most developed body structure as they age.